2012
DOI: 10.1063/1.4749817
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a 0.5 conductance plateau in asymmetrically biased GaAs quantum point contact

Abstract: We report the observation of a robust anomalous conductance plateau near G = 0.5 G0 (G0 = 2e2/h) in asymmetrically biased AlGaAs/GaAs quantum point contacts (QPCs), with in-plane side gates in the presence of lateral spin-orbit coupling. This is interpreted as evidence of spin polarization in the narrow portion of the QPC. The appearance and evolution of the conductance anomaly has been studied at T = 4.2 K as a function of the potential asymmetry between the side gates. Because GaAs is a material with establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 22 publications
2
19
0
1
Order By: Relevance
“…The details of the heterostructure layers are are the same as in ref. [27]. The 2DEG was characterized by Shubnikov-de Haas (SdH) and quantum Hall measurements; its carrier density and mobility were found to be 1.6×10 11 /cm 2 and 1.9×10 5 cm 2 /V-s, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The details of the heterostructure layers are are the same as in ref. [27]. The 2DEG was characterized by Shubnikov-de Haas (SdH) and quantum Hall measurements; its carrier density and mobility were found to be 1.6×10 11 /cm 2 and 1.9×10 5 cm 2 /V-s, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The 2DEG was characterized by Shubnikov-de Haas (SdH) and quantum Hall measurements; its carrier density and mobility were found to be 1.6×10 11 /cm 2 and 1.9×10 5 cm 2 /V-s, respectively. Sample cleaning and device fabrication procedure has been described elsewhere [27,28].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we showed that LSOC in InAs/InAlAs and GaAs/AlGaAs QPCs with in-plane side gates can be used to create a strongly spin-polarized current by purely electrical means in the absence of any applied magnetic field [7][8][9][10]. The use of a Non Equilibrium Green's Function (NEGF) approach to calculate the conductance of QPCs shows that the onset of spin polarization in devices with in-plane side gates required three ingredients: (1) an asymmetric lateral confinement, (2) a LSOC induced by lateral confining potential of the QPC, and (3) a strong electron-electron interaction [11,12].…”
mentioning
confidence: 99%
“…Notably, the conductance plateaus of some conductance traces prefer to locate at a conductance close to integer multiples of 0.5 G 0 ; this is similar to the results of etched Si/ SiGe quantum point contacts reported by Scappucci et al [21] and a 0.5 G 0 conductance plateau in a GaAs quantum point contact. [22] The characteristics of the conductance plateaus of germanium nanowires should be attributed to the electronic and mechanical properties of germanium.…”
Section: Conductance Measurements In the High-conductance Regionmentioning
confidence: 99%